Vitamin D receptor polymorphisms may contribute to asthma risk. (13th September 2016) - Han, Ji-Chang; Du, Jin; Zhang, Ya-Jun; Qi, Guan-Bin; Li, Hong-Bing; Zhang, Yi Jie; Yu, Xiao-ling
Abstract: Background: Asthma is a common chronic airway disorder associated with significant morbidity and mortality. Objective: Current study aims at investigating the correlation between four vitamin D receptor ( VDR ) gene polymorphisms and asthma susceptibility by conducting a meta-analysis. Methods: PubMed, EBSCO, Ovid, Wiley, Web of Science, Wanfang, CNKI and VIP databases were searched using combinations of keywords relating to VDR and asthma. The published studies were filtered using our stringent inclusion and exclusion criteria, and the resultant high-quality data from final selected studies were analyzed using Stata 12.0 software. Results: A total of 77 studies were initially retrieved, and after further selection, 9 studies were eligible in current analysis. The selected studies contained 2, 116 patients with asthma and 1, 884 healthy controls. Our results demonstrated that rs2228570, rs7975232 and rs731236 in both allele models and dominant models, and rs3782905 in allele model in the VDR gene were linked with a high risk of asthma. No significant association between VDR gene rs3782905 in dominant model and risk of asthma was detected. Conclusions: This meta-analysis provides convincing evidence that rs2228570, rs7975232, rs731236 and rs3782905 gene polymorphisms in VDR are associated with increased susceptibility to asthma, indicating VDR polymorphisms could be developed as biomarkers for asthma susceptibility.